Swearwords Used by Gangsters in the “Alpha Dog” Movie - Daniel Christian; Samuel Gunawan (Institute of Research and Community Outreach - Petra Christian University, 2014)
Many people assume that swearwords is a rude word and should be avoided. Those words are used to insult, to curse, to offend or to mock at something when the speaker has strong emotion (Hughes, 1991,05). To swear at someone or something is to insult and deprecate the object of abuse, as well as to use other kinds of dysphemism (Allan & Burridge, 2006,76). Apparently some experts and scholars have been able to prove that swearwords also has a purpose and a meaning beside the one as commonly held. Therefore, the writer took the